Efektivitas Media Komik Digital terhadap Keterampilan Membaca Pemahaman Siswa Kelas IV SD Inpres Kantisang Kota Makassar - Rezki Afriyanti Sukoco; Mayong Mayong; Asis Nojeng (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to describe students' reading comprehension skills before and after using digital comic media, and to measure the effectiveness of its use on the reading comprehension skills of fourth-grade students of SD Inpres Kantisang. The method used is quantitative with a one-group pretest-posttest design. The sample of the study was 25 fourth-grade students. Data were collected through multiple-choice tests analyzed using the SPSS version 30 application. The pretest results showed an average score of 50.8 with 3 students (12%) achieving completeness. After treatment using digital comic media, the average posttest score increased to 79.6 with 17 students (68%) achieving completeness. Normality and homogeneity tests showed that the data were normally distributed and homogeneous. The results of the paired sample t-test showed a significant difference (p = 0.01 < 0.05; tcount = 12.745 > ttable = 2.064). The average N-gain score of 0.60 is included in the medium category with a fairly effective level of effectiveness. Thus, digital comics have proven effective in improving students' reading comprehension skills, as they increase learning motivation and help students understand reading content in a more enjoyable way. Digital comics have demonstrated significant effectiveness in improving students' reading comprehension skills. This is due to their ability to present engaging learning, motivate students, and facilitate optimal comprehension of reading content.